Ketersediaan Fosfat, Serapan Fosfat, Dan Hasil Tanaman Jagung (Zea mays L.) Akibat Pemberian Kompos Granul Ela Sagu Dengan Pupuk Fosfat Pada Inceptisols - Maimuna La Habi; Jeanne Ivone Nendissa; Dessy Marasabessy; A. Marthin Kalay (Agrologia, 2018)
Inceptisol is a young and newly developed soil so it needs to be optimized for crop cultivation. The aim of this research is to know the availability of soil P, P uptake and corn yield after application of granular composting of sago waste (KGES) together with phosphate fertilizer to Inceptisols soil. The experimental treatment was KGES which consisted of three levels: without KGES, 40 tons KGES ha-1, and 80 tons KGES ha-1, and the use of SP-36 (P) fertilizer consisting of three levels: without P fertilizer, 120 kg P ha-1, and 240 kg P ha-1. The experiment used a complete randomized design with 3 replications. The result of the experiment was analyzed variance and relationship test using interlaced analysis. The results showed that KGES together with phosphate fertilizers could increase soil pH causing phosphate to be available and plant roots could absorb nutrient phosphate well, so that the yield of corn kiln dry weight also increased. The highest yield of dry weight of grains (7.85 tons per ha) was obtained from a combination of 80 tons of KGES ha-1 and 240 kg P ha-1.Keyword: Keywords: Ella Sago, Inseptisols, maize, phosphate